Pengembangan Aplikasi Geoheritage Berbasis Web di Desa Mengeruda, Kabupaten Ngada, Nusa Tenggara Timur Menggunakan Metode Scrum - Nurul Fitriani; Herliana Rosika; Moh. Ali Albar (Sekawan Institut, 2025)
Mengeruda Village, located in the Soa Basin, Ngada Regency, East Nusa Tenggara, possesses rich geological and local cultural potential that has not yet been optimally documented or published. This study aims to develop a web-based geoheritage application in Mengeruda Village, Ngada Regency, East Nusa Tenggara, as a medium for digital preservation and education. The development of the system was implemented using the Scrum methodology, which is divided into three phases: pre-game (needs analysis and planning), game (system development), and post-game (system testing). The primary features provided by the system consist of a cultural map, interactive 3D objects, photo and video galleries, and article content related to geoarchaeology, sociocultural aspects, and cultural sites. These features function as interactive learning media, comprehensive documentation of cultural heritage, and spatial representation of Mengeruda’s geoheritage and cultural assets. Additionally, the system is equipped with supporting features such as a news section and a profile page containing information about the village, the website, and the development team. Technically, the system was built using Tailwind CSS for a responsive interface, Leaflet.js for interactive mapping, and Express (Node.js) for the back-end. Functional testing was conducted using the Black Box Testing method with the Equivalence Partitioning technique, consisting of 16 test scenarios on the website for the admin actor. All scenarios were successfully executed with Passed status and met the defined specifications, indicating that the system has optimally fulfilled its functional aspects. Usability test using the System Usability Scale (SUS) was conducted with 40 respondents and resulted in a score of 77.625, which, according to Bangor (2009), falls within the Good and Acceptable categories. These results indicate that the developed system is suitable for use as a digital platform to support the promotion, preservation, and utilization of geoheritage and local culture by both the community and academic institutions.